Atomically dispersed Fe–Nx species within a porous carbon framework: an efficient catalyst for Li–CO2 batteries. Issue 12 (10th March 2022) - Ding, Junchao; Xue, Hairong; Xiao, Rui; Xu, Yunyun; Song, Li; Gong, Hao; Fan, Xiaoli; Chang, Kun; Huang, Xianli; Wang, Tao; He, Jianping
Abstract : We propose a metal–organic-framework-derived high-performance Fe–N–C electrocatalyst for Li–CO2 batteries. Abundant atomically Fe–N x active sites were formed in the porous carbon framework to provided catalytical sites with high activity. Abstract : Li–CO2 batteries are a promising energy storage system, while their practical application is still restricted by a lack of high-performance electrocatalysts for CO2 reduction and evolution reaction. Herein, we propose a metal–organic-framework-derived Fe–N–C electrocatalyst for Li–CO2 batteries. Within the Fe–N–C electrocatalyst, abundant Fe–N x active sites at the molecular level were formed in the porous carbon framework, profiting from a host–guest chemistry strategy between Fe–mIm nanoclusters and metal organic framework precursors in the pyrolysis process. The confinement effect of the metal organic framework host was beneficial to limit the Fe–mIm nanoclusters at the molecular level, thus resulting in the formation of Fe–N x sites with the high catalytic activity. Moreover, the as-prepared Fe–N–C catalyst is composed of dodecahedral nanoparticles stacking to form a unique three-dimensional structure with a large specific surface area and sufficient space, which not only favored the electron transport and CO2 /Li + diffusion but also promoted the deposition of discharge product Li2 CO3 to ensure a high capacity. Therefore, the Fe–N–C based Li–CO2 battery exhibits high specific capacity (13 238 mA h g −1 ), good rate capability and excellent cyclability (140 cycles). Therefore, these encouraging results suggest an effective approach to obtain high-performance Fe–N–C electrocatalysts for Li–CO2 batteries.